Drought risk and vulnerability in rainfed agriculture: Example of a case study from Australia - Stone R.C.; Potgieter A. (Drought management: scientific and technological innovations, 2008)
Many regions in Australia have extremely high levels of rainfall variability leading to periodically high drought risk for many agricultural enterprises. In this analysis, vulnerability and drought risk analysis methods incorporating Plant Available Water Capacity (PAWC) and soil moisture recharge levels are shown to have value in strategic planning for a rainfed crop and a pasture regime. Through input from specialist agronomists maps of PAWC at broad spatial scales for Australia have been produced. These maps show wide variation in drought vulnerability levels across Australia with levels of high vulnerability in some regions. Use of regional shire scale analysis illustrates important regional differences, important for strategic drought risk vulnerability assessments. For tactical-scale drought risk assessments, use of integrated PAWC, soil moisture recharge levels, crop simulation models and a climate forecasting system provides improved value.
1. International Conference Drought Management: Scientific and Technological Innovations, 2008/06/12-14, Zaragoza (Spain)